Diseño de un modelo de mejora continua de la gestión de proyectos para Anónima Operadora de Pensiones Complementarias - Álvarez-Gamboa, Manuel; Arce-Oses, Oscar Esteban (Instituto Tecnológico de Costa Rica, 2011)
The study explores the continuous improvement of the project management processes in ANÓNIMA OPC. The problem was defined as the identification of the features that a continuous improvement model must have, in order to encourage the organization taking advantage of the lessons learned and demonstrate that a better project management process performance has been achieved. The development of the model was based on the continuous improvement cycle proposed by the OPM3 standard: standardized, measure, control y improve, and in addition used the perspectives of the Balanced Scorecard. After a re-interpretation of those concepts, a project management’s continuous improvement model was designed focused on the project management’s success not on the maturity status. The project management success is calculated from the critical success factors defined: Cost Management, Time Management, Scope Management, Productivity Management and Quality Management. As a result of the weighing of the critical success factors results a general project management success is obtained. Due to the model’s target on the project management success will allow exploiting the lessons learned, because it is the main input for the analysis of the causes of the constraints for the project management success. Therefore this point of view may proof if real improvements in the project management processes are achieved through the success key performance indicators established.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, 2011.
Keywords: Estandarización; Gerencia; Indicadores; Éxito empresarial; Calidad; Información; Seguridad